Robust adaptive control for fractional-order systems with disturbance and saturation - Chen, Mou; Shao, Shuyi; Shi, Peng 1958- (The American Society of Mechanical Engineers, 2018)
Robust Adaptive Control for Fractional-Order Systems, with Disturbance and Saturation provides the reader with a good understanding on how to achieve tracking control and synchronization control of fractional-order nonlinear systems with system uncertainties, external disturbance, and input saturation. Although some texts have touched upon control of fractional-order systems, the issues of input saturation and disturbances have rarely been considered together.
Includes bibliographical references and index
Front Matter -- 1 Introduction -- 2 Fractional Calculus and Fractional-Order Systems -- 3 Fractional-Order PID Controller and Fractional-Order Disturbance Observer -- 4 Design of Fractional-Order Controllers for Nonlinear Chaotic Systems and Some Applications -- 5 Sliding-Mode Control for Fractional-Order Nonlinear Systems Based on Disturbance Observer -- 6 Disturbance-Observer-Based Neural Control for Uncertain Fractional-Order Rotational Mechanical System -- 7 Adaptive Neural Tracking Control for Uncertain Fractional-Order Chaotic Systems Subject to Input Saturation and Disturbance -- 8 Stabilization Control of Continuous-Time Fractional Positive Systems Based on Disturbance Observer -- 9 Sliding-Mode Synchronization Control for Fractional-Order Chaotic Systems with Disturbance -- 10 Anti-Synchronization Control for Fractional-Order Nonlinear Systems Using Disturbance Observer and Neural Networks -- 11 Synchronization Control for Fractional-Order Systems Subjected to Input Saturation -- 12 Synchronization Control for Fractional-Order Chaotic Systems with Input Saturation and Disturbance -- Back Matter. - System requirements: Adobe Acrobat Reader. - Mode of access: Internet via World Wide Web
Keywords: Technology & Engineering / Manufacturing / isacsh; Technology & Engineering / Quality Control / isacsh; Technology & Engineering / Robotics / isacsh; TECHNOLOGY & ENGINEERING / Engineering (General) / isacsh; Adaptive control systems; Adaptivregelung; Nichtlineare Regelung; Electronic books